Stabilization of lumbo-pelvic region and electromyography of the abdominal muscles - de Faria Negrão Filho, Rúben [UNESP]; de Brito Silva, P. [UNESP]; Ito, M. A. [UNESP]; Alves, Neri [UNESP]; Padovan, C. R. [UNESP]; Mícolis de Azevedo, F. [UNESP] (My University, 2006)
It is usual to find athletes that can perform de curl up test easily, but are unable to maintain the stabilization of the low back during the double straight leg lowering (DSLL). In spite of having strong abdominal muscles, its stabilization role seems not to be effective. Thus, the purpose of this study was to verify the relation among individuals with strong abdominal muscles and the ability in perform posterior pelvic tilt (PPT); the ability to stabilize the low back during the DSLL and the eletromyographic activity of the abdominal muscles. Eighteen male subjects (aged 19.27 ± 3.5), without history of muscle skeletal dysfunction, performed both the PPT and DSLL tests. During these tests electromyographic signals of the rectus abdominis (RA), obliquus internus abdominis (01) and obliquus externus abdominis (OE) were recorded, the angle of the hip and the pressure under the low back were measured The results of analyses of variance (ANOVA) show that most volunteers accomplished the PPT test, actively flattening the low back with regular or good quality. However, none of them was able to stabilize the low back during the DSLL test. During the PPT test all abdominal muscle portions analysed were activated without significant differences. In an attempt of maintaining the lumbo-pelvic region stabilized during the DSLL, it was observed a tendency of higher bilateral activation of OE when compared to RA and 01 muscle portions between 70 and 20 degrees of hip flexion.
Keywords: Abdominal muscles; Biomechanics; EMG; Lumbo-pelvic; abdominal wall musculature; adolescent; adult; analysis of variance; back; controlled study; electromyogram; external oblique muscle; hip; human; human experiment; internal oblique muscle; joint stability; lumbosacral spine; male; muscle contraction; muscle function; muscle strength; musculoskeletal disease; normal human; pressure measurement; rectus abdominis muscle; skeletal muscle; task performance; volunteer; Abdominal Muscles; Adolescent; Adult; Electromyography; Humans; Isometric Contraction; Leg; Lumbosacral Region; Male; Movement; Musculoskeletal Equilibrium; Pelvis; Reference Values